Effects of skipping one irrigation at different growth stages on yield and water productivity of some maize (Zea mays L.) cultivars under heavy clay soils of central Sudan - Mohammed, Hisham M.; Adam, Hussien S.; Idris, Siddig E.; Muhieldeen, Osama A. (Gezira Journal of Agricultural Science, 2017)
Crop production in arid and semi-arid regions faces the challenge to ensure high yields with limited supply of water. This study was conducted at the experimental farm of the Faculty of Agricultural Sciences, University of Gezira, during seasons 2014/15 and 2015/16. The objectives of this study were to investigate the effects of skipping one irrigation on yield and yield components of maize ( Zea mays L.). A split-plot design with four replicates was used. Main plots were assigned to the cultivars namely: Hudaiba1, Hudaiba2 and Mogtamaa -45, and sub-plots to irrigation treatments which consisted of (T 1 ) irrigation every 10 days throughout the season (control), skipping one irrigation at: Vegetative (T 2 ), flowering (T 3 ) and grain filling (T 4 ) stages. The results indicated that irrigation treatments and cultivars had highly significant effects on all parameters tested. Irrigation every 10 days resulted in the highest values of plant height, cob length, number of grains per cob, 100 seed weight, grain yield and water productivity. Hudaaiba2 outyielded the other two cultivars. Skipping one irrigation at flowering (T 3 ) stage gave the lowest values of the tested parameters. The highest grain yield was obtained when frequent irrigation (control) and Hudaiba 2 was practiced and the lowest was obtained by skipping of irrigation at flowering, which reflected the sensitivity of this stage for water deficit. Hence, it is recommended to grow Hudaiba2 maize cultivar and irrigate every 10 days.